Resurgent culture: being three lectures delivered at the University of Allahabad. - Krishnananda, Sri Swami (Tehri Garhwal, 1968)
Culture is a progressive transfiguration of nature, a creative activity of the evolving mind of man to approximate itself to perfection, so far as it is possible for it with the knowledge and energy with which it is endowed at a given level of life. The individual is neither a body merely, nor only a mind. The human individual, at least, is a composite structure, a complex of physical forces, vital urges, emotional stresses, moral aspirations and rational needs. Nothing that does not comprehend these in its compass or contribute to the training and development of these aspects can be called an integral culture. Culture is the reflection of the soul in man, and it is complete in proportion as it answers to the original, viz., internal perfection. Pure thought, decent speech, nobility of character, impartial love, truthfulness, honesty, straightforwardness, forbearance, such virtues as these are, there fore, the natural insignia of right culture, which can be regarded as an index of self-fulfilment. Culture implies voluntary self-restraint for the attainment of a higher goal.
Keywords: Culture